Erratum: Hyperons and massive neutron stars: vector repulsion and SU(3) symmetry [Phys. Rev. C 85, 065802 (2012)] - Weißenborn-Bresch, Simon Alexander; Chatterjee, Debarati; Schaffner-Bielich, Jürgen (Physical review. C, Nuclear physics, 2014)
DOI:https://doi.org/10.1103/PhysRevC.90.019904
Gesehen am 07.12.2020